High-performance GE/GESN photodetectors in near- and mid-infrared range - Son, Bongkwon (Nanyang Technological University, 2022)
Demand for Near- (NIR) and Mid-infrared (MIR) range detection has increased drastically for practical applications in optical sensing, imaging, and communications. Silicon (Si)-based photonic integrated circuits (PICs) have drawn attraction for such applications with cost-effectiveness, low power consumption, ultra-compact device footprint, and complementary metal-oxide-semiconductor (COMS) compatibility. However, Si is an indirect bandgap material with a bandgap of 1.12 eV, which makes it challenging to cover the wavelength beyond 1,100 nm. Although numerous efforts have been put into extending its cut-off wavelength, the large Si bandgap even restricts the whole NIR range photodetection. Germanium (Ge), a Group IV element, is CMOS compatible with an indirect bandgap of 0.66 eV. Since the direct conduction band of Ge bulk is located only 140 meV higher than the indirect band, a Ge photodetector is able to do NIR photodetection. Germanium-tin (GeSn) photodetectors have been introduced for MIR range photodetection, taking advantage of its bandgap tunability and excellent optical and electrical properties. An increase in Sn content shrinks GeSn bandgap and improves carrier mobility. In addition, GeSn lasers have been reported with direct bandgap properties, accelerating the development of the monolithic integration of Group IV-based optoelectronic integrated citcuits in the MIR range. As such, Ge and GeSn optical components are primarily attractive to NIR and MIR range applications, respectively. Nevertheless, III-V compound semiconductor photodetectors, e.g., indium gallium arsenide (InGaAs) photodetectors, dominate the industry despite their CMOS incompatibility, high complexity, and high cost. In order to utilize Ge/GeSn material systems for low-cost and CMOS compatible photodetectors, a low dark current and a high photon collection efficiency are required. During the epitaxial Ge/GeSn growth on a Si substrate, high density defects/dislocations are generated due to the large differences in the thermal expansion coefficient and lattice constants. The dislocations/defects act as trap states that degrade optical and electrical properties in Ge/GeSn material systems. Therefore, mitigation of defects in Ge/GeSn material systems should be implemented to improve optical performances. Direct wafer bonding (DWB) and layer transfer techniques enable a transfer of Ge/GeSn epitaxial layers directly on insulator platforms. The insulator platform improves not only optical confinement but also provides electrical isolation. In addition, defective Si/Ge/GeSn interfaces can be readily eliminated with the techniques, leading to enhanced photodetection in terms of dark currents and optical responsivities. This thesis explores high-performance Ge/GeSn photodetectors, which are fabricated on insulator platforms. In addition, furnace annealing in oxygen (O2) ambient and germanium-oxide (GeOx) formation via ozone (O3) oxidation are conducted to achieve a sub-mA/cm2 dark current for a Ge photodetector. Also, optical responsivity for the Ge photodetector is improved by gourd-shaped hole array structures. With these advanced techniques, improved detectivity is obtained, comparable to commercial Ge bulk and extended III-V photodiodes. GeSn alloys are investigated for MIR range photodetection. It is revealed that trap states near a Ge/GeSn interface degrade electrical and optical properties in GeSn material systems. In order to mitigate the trap-related carrier dynamics, waveguide GeSn photodetectors are demonstrated on an insulator platform. DWB and layer techniques enable the realization of a GeSn-on-insulator (GeSnOI) platform without the GeSn/Ge interface layer. A demonstrated GeSn photodetector on the GeSnOI platform provides the photodetection beyond 2,000 nm. The proposed Ge/GeSn photodetectors would be widely applicable to Si-based PICs for high-efficiency NIR and MIR range photodetection.